Peran Guru dalam Meningkatkan Motivasi Belajar Peserta Didik Underachiever di MI Modern SAKTI permatahati IBU Kepatihan Tulungagung - Chasanatul Mardiyah; Nur Kholis (Gerasi Insan Nusantara, 2023)
This research departs from the very complex phenomenon of the teacher's role in optimizing the potential of students. It is not uncommon for unrealized potential to become an obstacle in the learning process, such as being an underachiever. Through various roles, teachers try to help increase students' motivation to learn. The focus of this research is What is the role of the teacher as an educator, as a facilitator, and as an evaluator in increasing the learning motivation of underachiever students at MI Modern